Cecal perforation with an ascending colon cancer caused by upper gastrointestinal endoscopy - Hiroyuki Miyatani; Yukio Yoshida; Hirokazu Kiyozaki (Dove Medical Press, 2009)
Hiroyuki Miyatani1, Yukio Yoshida1, Hirokazu Kiyozaki21Department of Gastroenterology, Jichi Medical University, Saitama Medical Center, Saitama, Japan; 2Department of Surgery, Jichi Medical University, Saitama Medical Center, Saitama, JapanAbstract: Colonic perforation caused by upper gastrointestinal (GI) endoscopy is extremely rare. A 69-year-old woman was referred to our hospital because of abdominal fullness. Colonoscopy could be performed only up to the hepatic flexure due to an elongated colon and residual stools. Because her symptoms improved, upper GI endoscopy was performed 11 days later. The patient developed severe abdominal pain two hours after the examination. Abdominal X-ray and computed tomography showed massive free air. Immediate laparotomy was performed for the intestinal perforation. After removal of stool, a perforation site was detected in the cecum with an invasive ascending colon cancer. Therefore, a right hemicolectomy, ileostomy, and transverse colostomy were performed. Although she developed postoperative septicemia, the patient was discharged 38 days after admission. Seven months postoperatively, the patient died of lung, liver, and brain metastases. Even in cases with a lesion that is not completely obstructed, it is important to note that air insufflations during upper GI endoscopy can perforate the intestinal wall in patients with advanced colon cancer.Keywords: colonic perforation, colon cancer, upper gastrointestinal endoscopy, fecal peritonitis